Baicalin Inhibits Biofilm Formation and the Quorum-Sensing System by Regulating the MsrA Drug Efflux Pump in Staphylococcus saprophyticus - Wang, Jinli; Jiao, Haihong; Meng, Jinwu; Qiao, Mingyu; Du, Hongxu; He, Miao; Ming, Ke; Liu, Jiaguo; Wang, Deyun; Wu, Yi (Frontiers in Microbiology, 2019)
Staphylococcus saprophyticus (S. saprophyticus) is one of the main pathogens that causes serious infection due to its acquisition of antibiotic resistance. The efflux pump decreases antibiotic abundance, and biofilm compromises the penetration of antibiotics. It has been reported that baicalin is a potential agent to inhibit efflux pumps, biofilm formation and quorum-sensing systems. The purpose of this study was to investigate whether baicalin can inhibit S. saprophyticus biofilm formation and the quorum-sensing system by inhibiting the MsrA efflux pump. First, The mechanism of baicalin inhibiting efflux was investigated by the ethidium bromide (EtBr) efflux assay, measurement of ATP content and Pyruvate Kinase (PK) activities. These results revealed that baicalin significantly reduced the efflux of EtBr, the ATP content and the activity of PK. Moreover, its role in biofilm formation and the agr system was studied by Crystal violet staining, confocal laser scanning microscopy, scanning electron microscopy and Real-time polymerase chain reaction. These results showed that baicalin decreased biofilm formation, inhibited bacterial aggregation and downregulated mRNA transcription levels of the quorum-sensing system regulators agrA, agrC, RNAIII, and sarA. Correlation analysis indicated that there was a strong positive correlation between the efflux pump and biofilm formation and the agr system. We demonstrate for the first time that baicalin inhibits biofilm formation and the agr quorum-sensing system by inhibiting the efflux pump in S. saprophyticus. Therefore, baicalin is a potential therapeutic agent for S. saprophyticus biofilm-associated infections.